2006
DOI: 10.1007/s00360-006-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of slow type I myosin protein and mRNA expression in overwintering prairie dogs (Cynomys leucurus and ludovicianus) and black bears (Ursus americanus)

Abstract: Hibernating mammals have the remarkable ability to withstand long periods of fasting and reduced activity with dramatic maintenance of skeletal muscle function and protein composition. We investigated several hindlimb muscles of white-tailed prairie dogs (Cynomys leucurus) and black bears (Ursus americanus), two very different hibernators who are dormant and fasting during winter. The black-tailed prairie dog (C. ludovicianus) remains active during winter, but suffers minor skeletal muscle atrophy; nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 41 publications
9
40
2
Order By: Relevance
“…Recent studies assessing the relative expression of myosin isoforms in hibernating mammals have demonstrated either a fast to slow muscle fibre type transition or no change in fibre type. There were fast to slow shifts in proportional expression of myosin heavy chain in gastrocnemius and plantaris muscle in ground squirrels (Rourke et al, 2004;Nowell et al, 2011), and soleus in white tailed prairie dogs and biceps femoris in black bears (Rourke et al, 2006). However, there were no changes in myosin heavy chain expression in the soleus or diaphragm muscle in ground squirrels (Rourke et al, 2004), pectoral muscle in bats (Lee et al, 2008), gastrocnemius in black bears (Rourke et al, 2006) or biceps femoris in captive brown bears (Hershey et al, 2008).…”
Section: Assessment Of the Contractile Rate Of Skeletal Musclementioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies assessing the relative expression of myosin isoforms in hibernating mammals have demonstrated either a fast to slow muscle fibre type transition or no change in fibre type. There were fast to slow shifts in proportional expression of myosin heavy chain in gastrocnemius and plantaris muscle in ground squirrels (Rourke et al, 2004;Nowell et al, 2011), and soleus in white tailed prairie dogs and biceps femoris in black bears (Rourke et al, 2006). However, there were no changes in myosin heavy chain expression in the soleus or diaphragm muscle in ground squirrels (Rourke et al, 2004), pectoral muscle in bats (Lee et al, 2008), gastrocnemius in black bears (Rourke et al, 2006) or biceps femoris in captive brown bears (Hershey et al, 2008).…”
Section: Assessment Of the Contractile Rate Of Skeletal Musclementioning
confidence: 91%
“…There were fast to slow shifts in proportional expression of myosin heavy chain in gastrocnemius and plantaris muscle in ground squirrels (Rourke et al, 2004;Nowell et al, 2011), and soleus in white tailed prairie dogs and biceps femoris in black bears (Rourke et al, 2006). However, there were no changes in myosin heavy chain expression in the soleus or diaphragm muscle in ground squirrels (Rourke et al, 2004), pectoral muscle in bats (Lee et al, 2008), gastrocnemius in black bears (Rourke et al, 2006) or biceps femoris in captive brown bears (Hershey et al, 2008). Where significant changes in myosin heavy chain expression occur, we would expect concomitant alterations in the contractile rate of skeletal muscle (Harridge, 2007;Canepari et al, 2010).…”
Section: Assessment Of the Contractile Rate Of Skeletal Musclementioning
confidence: 94%
“…Namely, shivering in hibernating bears has been reported (Harlow et al, 2004;Toien et al, 2011), and this activity has been implicated in helping retard muscle atrophy during hibernation (Harlow et al, 2004;Rourke et al, 2006;Lohuis et al, 2007). However, the drastic reduction in weight-bearing activities implies that both the amounts of physiological mechanical loading and neural activation of the muscle are abnormally small.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that burrowing frogs might remodel and preserve existing muscle contractile proteins in the early stages of aestivation, precluding the requirement to transcribe actin and myosin genes in the middle and latter stages of dormancy. These findings are consistent with other studies of various species' of hibernating mammal which have shown that myosin heavy chain protein expression is often maintained despite prolonged muscle inactivity (Rourke et al, 2006;Rourke et al, 2004). While muscle contractile activity ceases during dormancy, skeletal muscle is also challenged to retain structural integrity despite disuse and starvation.…”
Section: Adherens Junction Remodellingsupporting
confidence: 92%